2009
DOI: 10.1590/s0102-311x2009000900013
|View full text |Cite
|
Sign up to set email alerts
|

Salud auto-referida y desigualdades sociales, ciudad de Buenos Aires, Argentina, 2005

Abstract: Self-rated health is a quality-of-life indicator. This study investigates the impact of individu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
(11 reference statements)
0
5
0
3
Order By: Relevance
“…Self-rated health is an indicator of the quality of life that Is related to the self-perception of an individual's health status 1 , 2 . Self-perception Is a practical method for collecting information on individual health since it entails a single aspect: a subject’s perception of his or her health status 1 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Self-rated health is an indicator of the quality of life that Is related to the self-perception of an individual's health status 1 , 2 . Self-perception Is a practical method for collecting information on individual health since it entails a single aspect: a subject’s perception of his or her health status 1 .…”
mentioning
confidence: 99%
“…Self-rated health is an indicator of the quality of life that Is related to the self-perception of an individual's health status 1 , 2 . Self-perception Is a practical method for collecting information on individual health since it entails a single aspect: a subject’s perception of his or her health status 1 . This information is useful for planning, implementing, and monitoring health initiatives and programs as it has been found that self-rated health is strongly associated with morbidity and mortality 3 - 8 , a relationship that remains after adjusting for physical, sociodemographic, and behavioural factors 3 - 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although PELFI is a longitudinal study, the current study of eye health has a transversal design, which limits the ability to establish a causal relationship between variables. The information about access to eye care specialists could be subject to recall bias, and the estimated self-perceived state of eye health could be inaccurate, given that it wasn’t measured objectively [10,39]. However, self-perceived health is used frequently in epidemiological studies because of its validity in predicting morbidity and mortality and its use in following population groups with specific health problems, in addition to the measurement of intervention effectiveness [40].…”
Section: Discussionmentioning
confidence: 99%
“…Possíveis diferenças quanto a associação entre a idade e autoavaliação de saúde, em universitários, podem estar condicionadas ao perfil etário desse grupo, de predomínio de jovens. Assim possíveis tendências de maiores prevalências de autoavaliação negativa de saúde com o aumento da idade, conforme observado em pesquisas de base populacional não foram observadas 2,5,25 . Alguns estudos mostram a associação entre hábitos alimentares inadequados e a autoavaliação negativa de saúde 6,26 .…”
Section: Discussionunclassified